Analisis Kompetensi dan Lingkungan Kerja dalam Meningkatkan Kinerja Pegawai (Studi kasus pada Koperasi Konsumen Praja Sejahtera Jawa Barat) - Dindin Burhanudin; Ivon Dwi Apriyanti (J-Coop : Journal of Co-operative, 2025)
This research aims to analyze the influence of competence and work environment on the performance of cooperative businesses. In the context of current economic development, cooperatives play a crucial role in enhancing community welfare. It is expected that human resource competence and work environment quality can significantly contribute to the performance of cooperative organizations. Through a quantitative approach, data was collected from various cooperatives using questionnaires distributed to cooperative managers and members. The analysis results indicate a positive relationship between competence and work environment with the performance of cooperative businesses. These findings provide recommendations for cooperative managers to enhance member competence and create a conducive work environment to improve overall business performance.